REPRESENTASI IDENTITAS GENDER PADA PLATFORM LIVE STREAMING GAME TWITCH.TV - Danumaya, Aditya (Universitas 17 Agustus 1945 Surabaya, 2020)
This study aims to determine the representation of gender identity on the live streaming game platform Twitch.tv. Gender performative theory assumes that humans produce identity, including gender through appearance or self-expression. At Twitch, basically communication takes place using an online medium. Streamers are given the freedom to represent their gender identity by creating content that can be seen by the public. This study uses a qualitative approach and uses Roland Barthes's semiotic analysis to determine the representation of identity displayed on verbal and nonverbal messages. The results are (1) Representation of feminine gender identity is shown by giving more personal information on the main page with words that indicate closeness rather than masculine; (2) Representation of feminine gender identity is shown by better maintaining relationships with audiences with personal conversations and telling in detail with the audience at the opening and closing of streaming content where masculine is more minimal; (3) Representation of feminine gender identity is shown by being more responsive to the ideas of the audience by providing space so that the audience can participate in communicating with streamers rather than masculine; (4) Representation of feminine gender identity is shown by being gentle in criticizing fellow gamers; (5) Representation of feminine gender identity is shown by emphasizing the tone of voice, maintaining eye contact to emphasize expression rather than masculine; (6) The selection of different artifacts according to gender identity in the form of choosing the color of clothes, type of clothes, dominance of the profile layout, background decoration and game characters presented.